FUNCTIONAL MAGNETIC RESONANCE ELECTRICAL IMPEDANCE TOMOGRAPHY (fMREIT) SENSITIVITY ANALYSIS USING AN ACTIVE BIDOMAIN FINITE ELEMENT MODEL OF NEURAL TISSUE - Sadleir, Rosalind J. (Magn Reson Med, 2018)
PURPOSE: A direct method of imaging neural activity was simulated to determine typical signal sizes. METHODS: An active bidomain finite element model was used to estimate approximate perturbations in MR phase data as a result of neural tissue activity, and when an external magnetic resonance electrical impedance tomography (MREIT) imaging current was added to the region containing neural current sources. RESULTS: Modeling predicted activity-related conductivity changes should produce measurable differential phase signals in practical MREIT experiments conducted at moderate resolution at noise levels typical of high field systems. The primary dependence of MREIT phase contrast on membrane conductivity changes, and not source strength, was demonstrated. CONCLUSION: Because the injected imaging current may also affect the level of activity in the tissue of interest, this technique can be used synergistically with neuromodulation techniques such as Deep Brain Stimulation, to examine mechanisms of action.